2000
DOI: 10.1177/107319110000700408
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the U.S. Presidents Using the Revised NEO Personality Inventory

Abstract: This article describes the use of objective psychological instruments, including the Revised NEO Personality Inventory (NEO PI-R), to assess the personalities of all 41 U.S. presidents to date. We briefly report our findings pertaining to the average profile of chief executives on the NEO PI-R and summarize data on two of our most illustrious presidents, Washington and Lincoln. We review a typology of presidents based on our data. Finally, we summarize the results of our investigation of the Big Five personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
103
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(110 citation statements)
references
References 28 publications
3
103
0
1
Order By: Relevance
“…-Previous studies and various sources (in particular: Cox, 1926;Rubenzer et al, 2000;Simonton, 1986a)…”
Section: Simonton (1984) European Hereditary Monarchsmentioning
confidence: 99%
“…-Previous studies and various sources (in particular: Cox, 1926;Rubenzer et al, 2000;Simonton, 1986a)…”
Section: Simonton (1984) European Hereditary Monarchsmentioning
confidence: 99%
“…Thus, it is very likely that the three measures, despite their distinct origins, are all tapping into the same underlying construct-each president's broad intellectual breadth, power, and energy. 1 As further support for this conjecture, the Openness scores also predict the performance ratings that the presidents receive from historians and political scientists who have expertise in the American presidency (Rubenzer, Faschingbauer, & Ones, 2000). In fact, not only does Openness predict presidential success better than any other Big Five factor, but it correlates with "ethics on the job" as well (Ones, Rubenzer, & Faschingbauer, 2004).…”
mentioning
confidence: 91%
“…Inspired by the pioneering research of Simonton (1986Simonton ( , 1987 on presidential personality, Rubenzer, Faschingbauer, and Ones (2000) found that some personality traits, most notably high levels of openness to experience (see also Simonton, 2006), extraversion, conscientiousness, and perhaps low levels of agreeableness, are modestiy correlated witii independentiy rated job performance among the U.S. presidents. Nevertheless, no study has examined the relation of psychopathic personality traits to leadership and job performance among the U.S. presidents.…”
mentioning
confidence: 98%